2. On-Line Production Monitoring and Control ? Introduction - F. L. Wilke (Society for Mining, Metallurgy & Exploration, 1979)
Underground mining is a very complicated and complex industrial activity. The uncertain and, in most cases, the incomplete knowledge of the geological and mineralogical nature of the deposits can cause unforeseen difficulties. For a safe and uninterrupted operation, in addition to good planning and scheduling, reliable and up-to-date monitoring and control of all processes and conditions become necessary. Today, this is even more important in view of increasingly difficult working conditions, poorer grades, and more complex and expensive machinery. In short, large capital investment and higher risk of financial losses are involved in modern-day mining operations. Monitoring and control of the underground mining process has become a very complex and difficult task in itself. Many different systems are available, and the correct choice .is of utmost importance from both the economic and safety points of view. This chapter will deal with aspects of underground production monitoring and control. There are, however, many other areas of equal importance which are covered in an excellent manner in a hand- book by Olaf (1976) on monitoring and control of underground operations.